Temporal correlation-based dynamic contrast-enhanced MR imaging improves assessment of complex pulmonary circulation in congenital heart disease - Tsai, Shang-Yueh; Wu, Ming-Ting; Lin, Yi-Ru; Hsieh, Kai-Sheng; Lin, Chu-Chuan; Huang, Teng-Yi; Chung, Hsiao-Wen; Pan, Jun-Yen; Huang, Yi-Luan; Pan, Huay-Ben; Yang, Chien-Fang (Magnetic resonance in medicine, 2006)
A temporal correlation (TC) mapping method is proposed to help bolus chasing during dynamic contrast‐enhanced (DCE) MRI of complex pulmonary circulation (CPC) in patients with congenital heart disease. DCE‐MRI was performed on five healthy male subjects (23–24 years old) and 25 patients (nine males and 16 females, 0.25–44 years old), and TC maps were generated by performing pixel‐based computation of cross‐correlations to the pulmonary artery with a series of time shifts in all subjects. Qualitative and quantitative evaluations were performed in comparison with original DCE images. TC maps exhibited a better signal‐to‐noise ratio (SNR) by factors of 4.3 and 1.3 in the lung parenchyma, pulmonary veins, and superior artery/vein; a better intraparenchymal contrast‐to‐noise ratio (CNR) by factors of 1.5–5.4; and a significantly higher conspicuity in all regions except the pulmonary arteries when graded with a five‐point score. TC maps evaluated by two experienced clinicians significantly added relevant information (P < 0.001), and in some cases affected the final diagnosis. We conclude that TC maps facilitate bolus chasing for DCE‐MRI by reducing recirculation effects and interframe fluctuations, and hence complements morphological imaging of CPC in patients with complex congenital heart disease. Magn Reson Med, 2006. © 2006 Wiley‐Liss, Inc.